Analysis of Integer Concept Understanding by Prospective Elementary School Teachers: Implications for Elementary Mathematics Teaching - Gusti Ngurah Sastra Agustika; I Nyoman Laba Jayanta; Dewi Anzelina (Journal Analytica Islamica, 2025)
Mathematics is an essential subject in elementary education, with integers playing a key role as the foundation for more complex mathematical concepts. However, many students struggle to understand integers, particularly negative numbers and their operations. This study aims to analyze how prospective elementary school teachers represent the concept of integers and develop effective teaching strategies. A qualitative descriptive approach was employed, involving 12 prospective teachers divided into three groups based on their understanding of integers. The primary instrument used was the modified Content Representation (CoRe) to evaluate how these prospective teachers represent and teach integers. The results indicate that most prospective teachers have a good grasp of basic integer concepts and frequently use number lines as a visual aid. However, some teachers still face difficulties in explaining negative numbers and their operations. The use of technology, such as interactive applications and educational videos, was recognized as an effective strategy for improving students' understanding. This study concludes that developing pedagogical skills in prospective teachers, particularly in teaching integers, is crucial to enhancing the quality of mathematics instruction at the elementary level.